2014
DOI: 10.1136/amiajnl-2013-002606
|View full text |Cite
|
Sign up to set email alerts
|

An integrative framework for sensor-based measurement of teamwork in healthcare

Abstract: There is a strong link between teamwork and patient safety. Emerging evidence supports the efficacy of teamwork improvement interventions. However, the availability of reliable, valid, and practical measurement tools and strategies is commonly cited as a barrier to long-term sustainment and spread of these teamwork interventions. This article describes the potential value of sensor-based technology as a methodology to measure and evaluate teamwork in healthcare. The article summarizes the teamwork literature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 50 publications
(51 reference statements)
0
53
0
Order By: Relevance
“…More objective measures of team-based primary care also are needed, because 44 of the 48 instruments identified depended on self-report. An especially promising avenue for future research may be the development of novel methods of team performance measurement that might leverage the growing field of health information technology (Rosen, Dietz, Yang, Priebe, & Pronovost, 2014). Finally, none of the instruments we identified have demonstrated that they are sensitive to change over time in the delivery of team-based care.…”
Section: Discussionmentioning
confidence: 87%
“…More objective measures of team-based primary care also are needed, because 44 of the 48 instruments identified depended on self-report. An especially promising avenue for future research may be the development of novel methods of team performance measurement that might leverage the growing field of health information technology (Rosen, Dietz, Yang, Priebe, & Pronovost, 2014). Finally, none of the instruments we identified have demonstrated that they are sensitive to change over time in the delivery of team-based care.…”
Section: Discussionmentioning
confidence: 87%
“…The use of video recording was reported more commonly than direct observation . A developing research technique is the use of sensors (such as radio frequency identification tags, infrared sensors and accelerometers) to record the position and movement of people or equipment . Teamwork in firefighters has been studied using smartphone sensors .…”
Section: Resultsmentioning
confidence: 99%
“…A major effort to extract information from medical devices as well as to motivate vendors to open their systems to the Emerge platform will be key to achieving the full potential of an integrated ICU. Over time, the inclusion of a growing number of automated data streams will enable better real time management of patients as well as the care team itself [ 18 ].…”
Section: Future Goalsmentioning
confidence: 99%